Linguistic Influence on Russian and American Ethnobiological Categorization - Nolan, Justin M.; Zaresheva, Aina; Robbins, Michael C. (Ethnobiology Letters, 2019)
In the Russian language, nouns are classified by gender and animacy, whereas in English, nouns are not. Using triad-sorts of names for biological and non-biological taxa, a comparison of results provided by native speakers of both languages reveals that cognitive categorizations of animate and inanimate nomenclatural forms differ significantly between speakers of Russian and American English. Speakers of American English appear to categorize names for living nouns more by phenotype than do Russians, who in turn appear to classify nouns more frequently on the basis of linguistic features such as gender. These results are believed to be pertinent to the elicitation and construction of folk ethnobiology taxonomies.